Throwing Foreign Aid at HIV/AIDS in Developing Countries: Missing the Target? - Peter Nunnenkamp; Hannes Öhler (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
We assess empirically whether foreign official development assistance (ODA) has been effective in alleviating HIV/AIDS epidemics, which figures prominently among the Millennium Development Goals. We employ a difference-in-difference-in-differences approach to identify the treatment effect of ODA specifically meant to fight sexually transmitted diseases on HIV/AIDS-related outcome variables. We do not find that ODA has prevented new infections to an extent that would have reduced the number of people living with HIV. By contrast, ODA has contributed effectively to the medical care of infected people. However, conclusive evidence on significant treatment effects on AIDS-related deaths only exists for the major bilateral source of ODA, the United States. In particular, targeted US assistance programs appear to be more effective than the activities of multilateral organizations.
Keywords: F35; I19; 330; HIV prevalence; AIDS-related deaths; official development assistance; aid effectiveness; major donors; difference-in-difference-in-differences